A hybrid simulation approach applied in sustainability performance assessment in make-to-order supply chains: The case of a commercial aircraft manufacturer. Issue 1 (2nd January 2023) - Barbosa, Cátia; Malarranha, Carlos; Azevedo, Américo; Carvalho, Ana; Barbosa-Póvoa, Ana
ABSTRACT: Make-to-order (MTO) supply chains (SC), common in aerospace industries, are very complex compared to mass production chains. Moreover, one of the significant long-term challenges is sustainability performance across its entire supply chain. However, this is not an easy task given the complexity involved, so decision support tools are fundamental instruments in understanding the entire supply chain from a sustainability performance perspective. Using simulation as a research method, this article proposes a hybrid and hierarchical performance assessment model, considering key sustainability indicators. The model is hybrid due to the use of different simulation methods– System Dynamics (SD), Discrete Event Simulation (DES), and Agent-based simulation (ABS). The model is applied to an aerospace manufacturer's real case to assess the sustainability performance of alternative SC. Unlike existing contributions, this work addresses the make-to-order supply chain from a sustainability performance perspective and does not compromise the representation of the diverse manufacturing functions and resources.